DIURNAL VARIATION IN THE CATCHES OF DEMERSAL FISHES IN THE NORTH WEST REGION OF BAY OF BENGAL DURING 1959-60 - Rao, T Appa; Moorthi, B Krishna (Indian Journal of Fisheries, 2011)
During the pericxl November 1959-Ootober 1960, the Government of India trawler M. T. Ashok carried out exploratory trawling for demersal fishes, both during day and night, off the coasts of Andhra and Orissa between latitudes 17Â°-40’ to 20Â°-10’ N and in depths ranging from 5 to 64 metres. Six major groups of fishes viz., sharks and skates, rays, catflshes miscellaneous big and small fishes and prawns in the catches showed diurnal variations. The catches of sharks, skates, miscellaneous fish and catfish were heavier during the day than night, irrespective of the area of capture and depth. Prawns and rays, however, yielded better catches at night. No definite trends could be seen in the seasonal variations of the above six groups in 17Â°-40’ N and 18Â°-10’ N latitude zones and also at two depth-ranges of 35-44 m and 45-54 m. Further, analysis was made of the seasonal variations of the six groups at two depth-ranges 35-44 m and 45-54 m, but no definite trends on their abundance could be discerned.